Short-term effects of cognitive training program for individuals with amnestic mild cognitive impairment: A pilot study - Sirinun Boripuntakul (2018)
This study examined the effects of a cognitive training program on cognitive function and neurochemistry changes in individuals with amnestic mild cognitive impairment (aMCI). Ten individuals with aMCI were randomly assigned to the experimental (n = 5) and control (n = 5) groups. The experimental group took part in an 18-session cognitive training program over a 6-week period. After completing the cognitive training course, the experimental group demonstrated significant improvement in memory, attention, and executive functions. With respect to the neurochemistry biomarkers, the myoinositol/creatine (mI/Cr) ratio was significantly decreased in the hippocampus, prefrontal cortex, and anterior cingulate cortex of the experimental group after training. Findings demonstrate that the cognitive training program showed promising evidence in improving cognitive functions in individuals with aMCI. The observed cognitive function improvement was accompanied by a decrease of mI levels. © 2012 by Informa Healthcare USA, Inc.